Изменения показателей общесоматического состояния при патологии органов брюшной полости и возможность их коррекции промыванием брюшной полости физиологическим раствором обогащенным ксеноном = Changes in state somatic abdominal pathology and possibility of their correction by washing the abdominal cavity with saline enriched xenon - A. A. Vasil'ev; A. I. Gozhenko; V. M. Sirman; B. A. Nasibullin (Kazimierz Wielki University, 2015)
Vasil'ev A. A., Gozhenko A. I., Sirman V. M., Nasibullin B. A. Изменения показателей общесоматического состояния при патологии органов брюшной полости и возможность их коррекции промыванием брюшной полости физиологическим раствором обогащенным ксеноном = Changes in state somatic abdominal pathology and possibility of their correction by washing the abdominal cavity with saline enriched xenon. Journal of Education, Health and Sport. 2015;5(9):739-746. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35720 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A739-746 https://pbn.nauka.gov.pl/works/685048 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011-2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015.   Изменения показателей общесоматического состояния при патологии органов брюшной полости и возможность их коррекции промыванием брюшной полости физиологическим раствором обогащенным ксеноном   CHANGES IN STATE somatic abdominal pathology and possibility of their correction by washing the abdominal cavity with saline enriched XENON   А. А. Васильев, А. И. Гоженко, В. М. Сирман, Б. А. Насибуллин A. A. Vasil'ev, A. I. Gozhenko, V. M. Sirman, B. A. Nasibullin   ГП "Украинский НИИ медицины транспорта МОЗ Украины", Одесса SE "Ukrainian Scientific Research Institute of Transport Medicine, Ministry of Health of Ukraine", Odessa   Summary There was an experimental study on the 290 rats weighing 180-220 gr. The authors stated that the enlargement of bad pathology of abdominal cavity (fecal or traumatic peritonitis, hepatic steatosis) provides variation of performance state indices. In case of red blood variation has a compensatory habit and leads to the support of carrier function. In case of white blood variation is typical for profuse xenobiotic stress. The usage of xenon relieves the demand of compensatory variation in red blood and favors hemogram recovery. The authors connect the salvage of performance state with the endointoxication depression that for its part is connected with positive xenon effect on the interseptum cell elements of abdominal cavity organs.   Key words: xenon, peritonitis, hepatic steatosis, blood.   Резюме Авторы в экспериментальных исследованиях на 290 крысах массой 180-220гр. показали, что развитие тяжелой патологии брюшной полости (каловый или травматический перитонит, жировой гепатоз) сопровождается изменениями показателей общесоматического состояния. В красной крови эти изменения носят компенсаторный характер и направлены на поддержание её транспортной функции, а в белой крови изменения характерны для массивной ксенобиотической нагрузки. Применение ксенона ослабляет необходимость компенсаторных изменений в красной крови и способствует нормализации формулы крови. Авторы связывают улучшение общего соматического состояния с ослаблением эндогенной интоксикации связанной с положительным влиянием ксенона на мембраны клеточных элементов органов брюшной полости.   Ключевые слова: ксенон, перитонит, жировой гепатоз, кровь.